(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
November 20 was incorporated into the civic calendar of Mexican national holidays in 1936. With this institutionalization, the date became a “place of memory” for all Mexicans and not a commemoration of a part of society, as it was assumed by the executive and ceased to be used solely by the PNR political party. During these years, in the commemorative narrative and in the speeches of the representatives of the government party and the State, it was established that through the commemoration of the Revolution, the popular masses who had carried out this process between 1910-1920 were vindicated. It was a recurrent use of the past and the present that was accompanied by the construction of an ethnographic discourse that had the intention of showing that the State and society were marching together towards the horizon of a united revolution.